Social representation of young people in higher education about sexually transmitted infections - Thelma Spindola; Laércio Deleon de Melo; Juliana de Lima Brandão; Denize Cristina de Oliveira; Sérgio Corrêa Marques; Cristina Arreguy-Sena; Paulo Ferreira Pinto (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to analyze the social representations about sexually transmitted infections elaborated by undergraduate students. Methods: a descriptive, qualitative study, in the light of the structural approach of Social Representation Theory, carried out with 160 young undergraduate students, in the second half of 2019, in the city of Rio de Janeiro. Data were collected using a sociodemographic characterization questionnaire, knowledge and practices for preventing sexually transmitted infections, analyzed using descriptive statistics and a form of free evocations with the inducing term STD, analyzed using prototypical and similarity analysis. Results: the representation's possible central nucleus is composed of lexicons aids, disease and HIV; the peripheral system by syphilis, sex, condoms, gonorrhea, prevention, infection, carelessness, HPV, herpes, ignorance, treatment, fear, unprotected-sex and danger. Final considerations: social thinking about sexually transmitted infections is characterized by their recognition as diseases, which require barrier prevention measures, associating with unsafe sexual practices that arouse fear.